Neptune's ring arcs confined by coorbital satellites: Dust orbital evolution through solar radiation - Giuliatti Winter, S. M. [UNESP]; Madeira, G. [UNESP]; Sfair, R. [UNESP] (Oxford University Press (OUP), 2020)
Here, we report the results of a set of numerical simulations of the system formed by Neptune, Galatea, dust ring particles, and hypothetical co-orbital satellites. This dynamical system depicts a recent confinement mechanism formed by four co-orbital satellites being responsible for the azimuthal confinement of the arcs. After the numerical simulations, the particles were divided into four groups: particles that stay in the arcs, transient particles, particles that leave the arcs, and particles that collide with the co-orbital satellites. Our results showed that the lifetime of the smaller particles is 50 yr at most. After 100 yr, about 20% of the total amount of larger particles are still present in the arcs. From our numerical simulations, the particles should be present in all arcs after 30 yr. Analysis of the dust production ruled out the hypothesis that small satellites close to or in the arc structure could be its source.
Keywords: planets and satellites: dynamical evolution and stability; planets and satellites: rings